Single‐Rate Dual‐Domain Mass Transfer Model: Elucidating Temperature Effects. Issue 4 (2nd April 2021) - Binder, M.; Hahnewald, A.; Händel, F.; Prommer, H.; Engelmann, C.; Burghardt, D.; Stock, P.; Tritschler, F.; Liedl, R.; Walther, M.
Abstract: In this study, the influence of varying temperatures on the transport behavior of conservative solutes in heterogeneous porous media has been investigated. Column flow experiments employing potassium bromide as tracer were conducted at four temperature levels (3°C, 10°C, 20°C, and 30°C) and the measured electrical conductivity (EC) signal was interpreted through inverse modeling. Additional experiments were performed with deuterium‐enriched water at 10°C and 30°C. For those experiments, deuterium isotope ratios were analyzed alongside anion and cation concentrations. Obtained EC‐based breakthrough curves showed measurable differences in both the observed peak values and tailing intensities that could be clearly attributed to variations in the experimental temperatures. The EC‐based results were further corroborated by the measured isotope ratios and corresponding anion/cation concentrations, although measured differences were less pronounced. The model‐based interpretation of the results employed the standard advection‐dispersion equation as well as three alternative variants that were all based on the single‐rate dual‐domain mass transfer (DDMT) approach, but embracing varying coupling intensities between the experiments. For all variants transport parameters were determined for EC, bromide, and deuterium, respectively. The estimated ranges of the transport parameters all point toward a direct correlation between the effective DDMT rates and the experimental temperature. The observed correlation directly follows the Arrhenius relationship, but is weaker than the one describing the temperature dependence of the molecular diffusion coefficients, therefore pointing to a contribution of non‐diffusive components. Key Points: Comparative column tracer experiments were conducted at four temperature levels Magnitude of dual‐domain mass transfer rate correlates with experimental temperature Observed temperature dependence can be approximated by the Arrhenius relationship